UPAYA PENINGKATAN LITERASI KEUANGAN ANGGOTA POKDARWIS “DEWI JEPANG” MELALUI PELATIHAN KEUANGAN DI DESA JERU KECAMATAN TUMPANG KAB MALANG - Nugraha, Adri Putra; Fitriasari, Rizka; Firdaus, Rizalnur (Jurnal Likhitaprajna, 2023)
Financial management is an important aspect in managing tourism business, however, the members of Dewi Jepang Pokdarwis in Jeru Village, Malang Regency have limited understanding and skills in financial management for tourism micro-enterprises. This can impact the implementation of transparency and accountability principles in financial management and reduce stakeholder trust in Pokdarwis' performance. Therefore, a financial literacy training was conducted as a participatory community service activity aiming to improve the knowledge and capacity of Pokdarwis members in managing tourism business finances. The training was planned using a participatory approach by actively involving Pokdarwis as partners from planning, implementation to evaluation. Training materials covering basic concepts to financial analysis were developed based on partners' direct input to match the needs of micro-scale tourism financial management. The training was implemented interactively through lectures, case studies, group discussions and practices over 2-3 days. Evaluation showed the training significantly improved participants' understanding, as the percentage of participants scoring above 80% increased from initial 15% to majority 16 people or 80%. Monitoring and regular mentoring after training were also conducted to assess implementation and potential improvements. It is expected this training can enhance Pokdarwis' financial management performance and empower local community's economic potential.